2022
DOI: 10.3389/fvets.2021.799065
|View full text |Cite
|
Sign up to set email alerts
|

The First Lumpy Skin Disease Outbreak in Thailand (2021): Epidemiological Features and Spatio-Temporal Analysis

Abstract: The first outbreak of lumpy skin disease (LSD) in Thailand was reported in March 2021, but information on the epidemiological characteristics of the outbreak is very limited. The objectives of this study were to describe the epidemiological features of LSD outbreaks and to identify the outbreak spatio-temporal clusters. The LSD-affected farms located in Roi Et province were investigated by veterinary authorities under the outbreak response program. A designed questionnaire was used to obtain the data. Space-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 47 publications
(54 reference statements)
5
56
0
Order By: Relevance
“…Although LSDV has spread from Africa to the Middle East and East Europe since 2012, the disease only reached East and South Asia in 2019, affecting China, India, Bangladesh, Bhutan, Vietnam, Thailand, Hong Kong, and Myanmar [ 38 , 39 ]. The first suspected LSD cases in Nepal were reported in June 2020 in the Morang district near the Indian border and were confirmed by molecular techniques [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although LSDV has spread from Africa to the Middle East and East Europe since 2012, the disease only reached East and South Asia in 2019, affecting China, India, Bangladesh, Bhutan, Vietnam, Thailand, Hong Kong, and Myanmar [ 38 , 39 ]. The first suspected LSD cases in Nepal were reported in June 2020 in the Morang district near the Indian border and were confirmed by molecular techniques [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…All dairy cattle on each farm that participated in the study were examined by veterinarians for clinical signs of LSD. Similar to a previous report ( 23 ), an LSD animal case was defined as a dairy cow displaying the LSD clinical signs, which include raised firm nodules with a diameter of 1–7 cm on the head and/or body surface areas. Notably, veterinarians conducting outbreak investigations did not collect animal samples to confirm LSD infections.…”
Section: Methodsmentioning
confidence: 99%
“…Data collected by livestock authorities as part of the LSD outbreak investigation and control program in March 2022 revealed that the total number of beef and dairy cattle affected by LSD was 609,073, and 12,317, respectively ( 22 ). During the outbreaks, both beef and dairy cattle were affected by LSD, which resulted in poor health and decreased production ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations